Continuous production of eugenol esters using enzymatic packed‐bed microreactors and an evaluation of the products as antifungal agents. (14th February 2019) - Giovannini, Pier Paolo; Catani, Martina; Massi, Alessandro; Sacchetti, Gianni; Tacchini, Massimo; de Oliveira, Débora; Lerin, Lindomar Alberto
Abstract: The enzymatic synthesis of biologically active compounds is receiving increasing interest from academic and industrial researchers. Herein, we report on the continuous‐flow enzymatic production of eugenol esters with packed‐bed microreactors prepared with the Novozym 435 and Lipozyme RM IM lipases. After optimization of the independent process variables, namely temperature (68 °C), flow rate (8 μL min −1 ), and eugenol/isobutyric anhydride molar ratio (1 : 5) by means of experimental design methodologies, the unprecedented continuous‐flow production of eugenyl isobutyrate has been achieved with steady‐state conversions of 77 and 70%, using packed‐bed microreactors prepared with Novozym 435 and Lipozyme RM IM, respectively. With acetic anhydride as the acylating agent, the same reactors, under the same conditions, afforded eugenyl acetate with steady‐state conversions of 82% (Novozym 435) and 90% (Lipozyme RM IM). The two ester products have been tested against phytopathogenic and dermatophytic fungi, demonstrating interesting action against dermatophytic fungi. The reported results demonstrated the suitability of the enzymatic packed‐bed microreactors as a sustainable and scalable technology for the solvent‐free continuous‐flow production of biologically active esters of eugenol. Abstract : We report the optimization of continuous‐flow enzymatic production of eugenol esters with packed bed micro‐reactors, and the esters produced were tested against phytopathogenic and dermatophytic fungi, demonstrating interesting action against dermatophytic fungi.